Molecular Detection of Bartonella quintana among Long-Tailed Macaques (Macaca fascicularis) in Thailand - Wanat Sricharern; Supakarn Kaewchot; Phirabhat Saengsawang; Sarawan Kaewmongkol; Tawin Inpankaew (Pathogens, 2021)
Bartonella quintana is a zoonotic pathogen with a worldwide distribution. Humans and non-human primates are considered to be natural reservoir hosts for B. quintana. However, information on the molecular epidemiology of this organism is very limited in regard to long-tailed macaques (Macaca fascicularis) in Thailand. Therefore, this study aimed to investigate the occurrence and genetic diversity of Bartonella spp. among long-tailed macaques in Thailand. In total, 856 blood samples were collected from long-tailed macaques in Thailand. All specimens were screened for Bartonella spp. using a polymerase chain reaction (PCR) assay targeting the 16S rRNA, gltA and ftsZ genes. All positive samples were further analyzed based on nucleotide sequencing, phylogenetic analysis and multiple sequence alignment analysis. Only one macaque showed a positive result in the PCR assays based on the 16S rRNA, gltA and ftsZ genes. Nucleotide sequencing and phylogenetic analysis revealed that the obtained sequences were closely related to B. quintana previously detected in non-human primates. Single-nucleotide polymorphisms (SNPs) were detected in the gltA and ftsZ gene sequences. This study revealed that long-tailed macaques in Thailand carried B. quintana. Despite the low infection rate detected, long-tailed macaques may be a reservoir of B. quintana.